RET splice site variants in medullary thyroid carcinoma - Saeed-Vafa, Daryoush; Chatzopoulos, Kyriakos; Hernandez-Prera, Juan; Cano, Pedro; Saller, James J.; Hallanger Johnson, Julie E.; McIver, Bryan; Boyle, Theresa A. (Frontiers in Genetics, 2024)
Medullary thyroid cancer (MTC) is an aggressive cancer that is often caused by driver mutations in RET. Splice site variants (SSV) reflect changes in mRNA processing, which may alter protein function. RET SSVs have been described in thyroid tumors in general but have not been extensively studied in MTC. The prevalence of RET SSVs was evaluated in 3,624 cases with next generation sequence reports, including 25 MTCs. Fisher exact analysis was performed to compare RET SSV frequency in cancers with/without a diagnosis of MTC. All 25 MTCs had at least one of the two most common RET SSVs versus 0.3% of 3,599 cancers with other diagnoses (p<0.00001). The 11 cancers with non-MTC diagnoses that had the common RET SSVs were 4 neuroendocrine cancers, 4 non-small cell lung carcinomas, 2 non-MTC thyroid cancers, and 1 melanoma. All 25 MTCs analyzed had at least one of the two most common RET SSVs, including 4 with no identified mutational driver. The identification of RET SSVs in all MTCs, but rarely in other cancer types, demonstrates that these RET SSVs distinguish MTCs from other cancer types. Future studies are needed to investigate whether these RET SSVs play a pathogenic role in MTC.